1999
DOI: 10.1002/(sici)1520-6300(199909/10)11:5<577::aid-ajhb1>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased tooth crown size in females with twin brothers: Evidence for hormonal diffusion between human twins in utero

Abstract: In rodents, the position of a fetus in utero is associated with the expression of sexually dimorphic traits. This phenomenon has been explained by prenatal diffusion of sex hormones among litter mates. To test for such effects in humans, female‐male twin pairs provide a natural experiment. The size of dental crowns is a sexually dimorphic trait which can be measured with a high degree of reliability. Thus, two crown diameters of 28 permanent teeth were recorded for 56 opposite‐sexed (OS) and 242 same‐sexed (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 38 publications
3
37
1
Order By: Relevance
“…Most studies failed to find differences between OS and SS females on a variety of measures of reproductive characteristics and handedness. Exceptions concerned tooth size [194] and spontaneous otoacoustic emissions, an auditory characteristic that shows sex differences and is related to hearing sensitivity [178]: in both cases OS females were masculinized relative to SS females. In contrast, click-evoked otoacoustic emissions, another auditory characteristic that shows sex differences and is related to hearing sensitivity [179], did not differ significantly between OS and SS females, although OS females were considered by the investigators to show 'masculine' changes and the overall results were interpreted to suggest that prenatal exposure to testosterone leads to a more masculinized pattern of otoacoustic emissions [180].…”
Section: Physical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies failed to find differences between OS and SS females on a variety of measures of reproductive characteristics and handedness. Exceptions concerned tooth size [194] and spontaneous otoacoustic emissions, an auditory characteristic that shows sex differences and is related to hearing sensitivity [178]: in both cases OS females were masculinized relative to SS females. In contrast, click-evoked otoacoustic emissions, another auditory characteristic that shows sex differences and is related to hearing sensitivity [179], did not differ significantly between OS and SS females, although OS females were considered by the investigators to show 'masculine' changes and the overall results were interpreted to suggest that prenatal exposure to testosterone leads to a more masculinized pattern of otoacoustic emissions [180].…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…Therefore, they examined the traits described above in studies of females. Most studies failed to find demasculinization in males with a female co-twin on physical traits, such as tooth size [194], psychological traits, such as social attitudes [189] and sensation-seeking [62], spatial ability [186], sex-typed toy play [193], and handedness [185]. Interestingly, however, there is some suggestion that males with a female co-twin might be demasculinized or feminized on gender-role behavior [190,191], but it is not possible to know whether this reflects effects of gestating in proximity to a female or being reared with one.…”
Section: Findings: Physical and Behavioral Traits In Oppositesex Malementioning
confidence: 99%
“…Previous twin studies supporting the TTT hypothesis have demonstrated increased masculine traits in human females from opposite-sex twin pairs as opposed to same-sex twin pairs. Examples include increased total brain volume [14], altered craniofacial growth and dental asymmetries [15], increased symptoms of Alcohol Use Disorder (AUD) [16], lower disordered eating attitudes [17] and increased tooth crown size [4,5]. These findings not only support the TTT hypothesis but also indicate that hormonal transfer may influence sensitivity of androgen receptors later in life (i.e.…”
Section: Introductionmentioning
confidence: 86%
“…Sexual dimorphism in the human craniofacial complex has also been related to the growth promoting effects of the Y-chromosome [2,3] and sex hormones [4,5]. In the dentition, sexual dimorphism has been described in tooth size [6], arch dimensions [7,8] and underlying bone size [3], suggesting common influencing factors on dental and craniofacial development.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have proposed that sexual differences are regulated by sex chromosomes [1,2], but there are some who have suggested that hormonal influences are also important [3,4]. Sexual dimorphism in human dentition and dermatoglyphs have been studied separately, and results are fairly consistent: males have larger tooth crown diameters than females [5,6], sexual dimorphism is greater in permanent than in primary teeth [6,7] and adult males have fewer finger ridges than females [8,9].…”
Section: Introductionmentioning
confidence: 99%